Prediksi Pergerakan Saham Menggunakan Metode Simulasi Monte Carlo untuk Pembentukan Portofolio Optimal dengan Pendekatan Model Markowitz - Megawati Megawati; Resmawan Resmawan; Boby Rantow Payu; Amanda Adityaningrum (Program Studi Statistika FMIPA UNJ, 2022)
Stock movements that follow a stochastic process move randomly at certain times, have led stock prices challenging to predict. For this reason, the monte carlo simulation method is used to get the possibilities of stock prices in the future. This case study focused on the shares listed on the Jakarta Islamic Index 70 in 2018, by simulating 10 times the daily closing price data, thus, the possible stock prices in 2019 were obtained. Portfolio optimization was then carried out using the markowitz model approach from the predicted data. Based on the prediction data, there are 20 stock have a positive expected return. The stocks that has the largest weight is ICBP.JK (Indofood CBP Sukses Makmur Tbk) stocks, with 0.1396, while the stocks with the smallest weight is INAF.JK (Indofarma (Persero) Tbk) at 0.0053. Histirical simulations calculate the Value a Risk of 20 stocks that provide optimal returns, if investors invest Rp. 100,000,000.00 the maximum risk or loss that will be obtained is Rp. 2,910,410.00 for 1 year.